Atelier sur la Fixation Biologique d`Azote du Haricot en Afrique = Workshop on Biological Nitrogen Fixation of Beans in Africa (1988, Rubona, Rwanda). Actes = Proceedings - Nyabyenda, P; Hakizimana, A; Kipe-Nolt, Judith A.; Davis, J.; Graf, W (International Center for Tropical Agriculture, 1988)
The background and current status of research on bean N fixation in Rwanda, Burundi, Zimbabwe, Tanzania, Malawi, Uganda, and Ethiopia are summarized. The 4 stages of the methodological framework for bean N fixation research of CIAT are described: (I) (a) Rhizobium strain isolation and characterization and (b) effectiveness of the symbiosis with native strains; (II) improvement of the symbiosis through inoculation and plant breeding; (III) management of agronomic and environmental factors; and (IV) inoculant production/inoculation methods. The lab of Institut des Sciences Agronomiques du Rwanda. and the main results of on-farm trials are reported. The projects proposed for future research are included and the discussion topics of the meeting are summarized. (CIAT)